Potassium channel structure: domain by domain. - Biggin, P; Roosild, T; Choe, S (2000)
Since the determination of the structure of a bacterial potassium channel, the ion channel community has managed to gain momentum in the quest for a complete picture. The information is coming at a steady flow, on a domain by domain basis. Recent discoveries are starting to reveal clues to the complex manner in which potassium channels show enormous diversity of function and also to their methods of regulation. Currently, the structures of four domains are known, with the most recent addition being the Kvbeta structure. As efforts continue in the study of the transmembrane domains, especially the voltage-sensing apparatus, there has been a new realization with respect to the identification and role of the cytoplasmic domains in protein-protein interactions in particular. An additional discovery, considerably aided by recent genomic analysis, is that potassium channels comprising subunits with two pore regions and four transmembrane helices combined in a dimeric fashion are abundant and are probable targets for local anesthetics.